What Happened to Pike's Animals - Bob Gress (Symphony in the Flint Hills, 2009)
In 1806 the Zebulon Pike Expedition passed through what is now Kansas for the purpose of "exploring the internal parts of Louisiana." At that time, all of Kansas was part of the recently acquired Louisiana Purchase of 1803. On Sept. 10, 1806, they were at the divide between the Neosho and the Verdigris rivers and on Sept. 11 camped near Bazaar in Chase County. On Sept. 12, 1806, he was very near the site of this, the 2009 Symphony in the Flint Hills location. Here, he made reference and was since credited with naming the Flint Hills. This article is a detail of each animal he saw and what their current status is in modern times.
Keywords: animals; native; hunting; extinction; Native Americans; Expedition; Indians; buffalo; wildlife; Kansas; Flint Hills; grassland; prairie; plains; elk; deer; cabrie; panthers